Preconceito linguístico, estigmas e silenciamento: um estudo de caso de um aluno brasiguaio - Alves, Lidiane de Carvalho (2022)
In the Triple Frontier region - Brazil, Paraguay, and Argentina -, it is not uncommon for the Enrollment and school initiation of Brazilians in schools in the city of Foz do Iguaçu (PR). These children, daughters of Brazilian parents, attended part of their lives in school in Paraguay. Due to the vision of linguistic homogenization of Portuguese, adopted by the Brazilian school, become socially stigmatized. Against this reality, this research, linked to Educational Sociolinguistics, sought to answer the following question: What are the implications for the student’s school life Brazilian who enrolls in a school, in a country different from the one in which he was literate, and is exposed to situations in which command of a language is required different from what you're used to? The main objective was to understand how the life student experience of a Brazilian student is affected by linguistic prejudice and what are the consequences of this practice. In addition, we seek to verify whether there is, on the part of a municipal school in Foz do Iguaçu, some reception procedure language course for Brazilian/foreign students. Methodologically, it is research of a qualitative nature, using the typology case study only. We used the semistructured interview as an instrument to generate data, carried out with the subjects participating in the study - a Brazilian student, then his mother, his teacher, and the coordinator of the João da Costa Viana Municipal School. The generated data were discussed and interpreted considering the precepts of Educational Sociolinguistics, under the bias of Culturally Sensitive Pedagogy, also making use of the perspective of Translinguagem. The results reveal that the student is silenced by linguistic prejudice in the school context, not only because of students but also by teachers, whether due to their way of speaking and writing or the stereotype that they have a low school performance. Still, because of these experiences and discourses, and ideologies built around being Brazilian, he has a self-perception of inferiority. Concerning reception brasiguaios/foreigners, on the part of the school, there is no established procedure in the municipality of Foz do Iguaçu. The teacher and coordinator who participated in this study revealed the lack of training and specific guidance on the particularities of the border school context and on teaching approaches in differentiated and inclusive ways that could be used. In conclusion, it is necessary that in cross-border spaces, develop a Culturally Sensitive, to welcome all students, but especially those who were silenced and marginalized, as is the case of Brazilians.